2006
DOI: 10.1007/s10038-006-0041-1
|View full text |Cite
|
Sign up to set email alerts
|

Similarity of the allele frequency and linkage disequilibrium pattern of single nucleotide polymorphisms in drug-related gene loci between Thai and northern East Asian populations: implications for tagging SNP selection in Thais

Abstract: The similarity of the marker allele frequency and linkage disequilibrium structure between two populations are major factors for the determination of the transferability and efficiency of haplotype tagging SNP derived from one population to use for an indirect association study in another population. To prove the similarity between northern East Asian populations in Hapmap and Thais, 861 SNP in 166 drug-related genes shared between Thais, Han Chinese and Japanese were analyzed for their correlation statistics.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 29 publications
2
19
0
Order By: Relevance
“…High transferability has also been reported for drug-related genes (Mahasirimongkol et al 2006). We therefore conclude that tagging SNPs selected from CHB + JPT captures common variants well, at least in Thais and probably in Southeast Asians as a whole, and that the genotype information of CHB + JPT is very useful for association studies in Southeast Asians.…”
Section: Discussionsupporting
confidence: 56%
“…High transferability has also been reported for drug-related genes (Mahasirimongkol et al 2006). We therefore conclude that tagging SNPs selected from CHB + JPT captures common variants well, at least in Thais and probably in Southeast Asians as a whole, and that the genotype information of CHB + JPT is very useful for association studies in Southeast Asians.…”
Section: Discussionsupporting
confidence: 56%
“…The strong correlations observed between Cebu Filipino samples and HapMap Asian panels are broadly consistent with other assessments of tagging transferability outside the HapMap ENCODE regions (Weale et al 2003;Nejentsev et al 2004;Ke et al 2005;Mueller et al 2005;Ramirez-Soriano et al 2005;Evans and Cardon 2005;Gonzalez-Neira et al 2006;Huang et al 2006;Mahasirimongkol et al 2006;Montpetit et al 2006;Ribas et al 2006;Willer et al 2006).…”
Section: Discussionsupporting
confidence: 85%
“…Studies that examined many populations worldwide found Asian and Oceania populations to be most similar to the Asian HapMap panel tested (Conrad et al 2006 andGonzalez-Neira et al 2006). Two studies have investigated the tagging transferability between the HapMap CHB, JPT, and CHB + JPT with sample sets from Thailand and from Korea (Mahasirimongkol et al 2006;Yoo et al 2006). A combination of tag SNPs from CHB + JPT best captured the LD structure of the Thais, while SNP selection based on JPT was most transferable to the Korean samples.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Populations in these regions were highly similar to each other and also close to the HapMap Chinese population. 13 All cases were human immunodeficiency virus-seronegative when TB was diagnosed, and the diagnosis of TB was confirmed by microscopic identification or mycobacterial culture.…”
Section: Japanese and Thai Genome-wide Association Samplesmentioning
confidence: 99%